Berberine promotes IGF2BP3 ubiquitination by TRIM21 to induce G1/S phase arrest in colorectal cancer cells. (1st April 2023) - Gui, Zhenwei; Li, Jingwei; Li, Juan; Li, Xiaoduo; Chen, Lihong; Ma, Zhengcai; Tang, Xiang; Gong, Xiaobao; Chai, Xue; Lu, Fangfang; Li, Mengmeng; Ma, Hang; et al.
Abstract: The increasing incidence of colorectal cancer (CRC) has become a major global public health burden. The natural drug Berberine (BBR) has shown potential in preventing CRC, and IGF2 mRNA binding protein 3 (IGF2BP3) may be a target of BBR. This study aims to investigate the mechanisms of BBR acting on IGF2BP3 to improve CRC. The results showed that IGF2BP3 played an important role in the development of CRC. BBR down-regulated IGF2BP3 expression and inhibited CRC growth in mice. Cell thermodynamic stability analysis (CETSA) and drug affinity responsive target stability (DARTS) analysis showed BBR may bind to IGF2BP3. BBR may induce structural changes in IGF2BP3 and decrease its protein stability in cytoplasm. The results from Co-Immunoprecipitation (Co-IP) suggested that BBR promoted the ubiquitination of IGF2BP3 by tripartite motif-containing protein 21 (TRIM21). Through RNA binding protein Immunoprecipitation (RIP) assay, it was found BBR inhibited the stabilization of CDK4/CCND1 mRNA by IGF2BP3 and promoted G1/S phase arrest in CRC cells. Overexpression of IGF2BP3 in vitro and in vivo attenuated the inhibition of CRC growth by BBR. This work demonstrated the potential of BBR targeting to IGF2BP3 in improving CRC and provided a new strategy for clinical treatment on CRC as well as novel anticancer drug design based on IGF2BP3 and TRIM21. Graphical abstract: Image 1 Highlights: BBR promotes the ubiquitination of IGF2BP3 by TRIM21 in CRC cells. BBR inhibits the stabilization of CDK4/CCND1 mRNA by IGF2BP3 in CRC cells. BBR binds to IGF2BP3 and reduces its protein stability in the cytoplasm of CRC cells.